Catherinum flavum - Shalaeva, Kate; Boxshall, Geoff (Zenodo, 2014)
Catherinum flavum (Hoek, 1883) Fig. 20 Scalpellum flavum Hoek, 1883: 127, pl. VI, fig. 9, pl. X, figs 7–9. Catherinium flavum : Zevina, 1981a: 253, fig. 188. Material examined. Three full-grown syntypes (two of them deteriorated) NHM UK 2013.1098–1100 and additional material (see remarks) NHM UK 2013.1101-1102, Stn 146: Indian Ocean, Antarctic and Southern (North-east of Prince Edward Island); 2515 m. Diagnosis. The only diagnosis is that of Hoek (1883), which includes description of the appendages. Distribution. Indian Ocean, Antarctic and Southern. Known depth 2515 m. Remarks. A thorough redescription of the appendages is needed. Hoek (1883) based his description on three “full-grown specimens” from Stn 146. The jar in the NHM collection contains two vials: one with two large (Fig. 20 A, B; capitulum length 8 mm) and one medium size (Fig. 20 C; capitulum length 5 mm) specimens, the other with one medium size specimen (Fig. 20 D; capitulum length 6 mm), one small specimen and some fragments. We infer that the former vial contains the three specimens mentioned by Hoek (1883). The latter vial is treated as additional material, and should not be accorded type status. Published as part of Shalaeva, Kate & Boxshall, Geoff, 2014, An illustrated catalogue of the scalpellid barnacles (Crustacea: Cirripedia: Scalpellidae) collected during the HMS " Challenger " expedition and deposited in the Natural History Museum, London, pp. 1-63 in Zootaxa 3804 (1) on page 32, DOI:10.11646/zootaxa.3804.1.1, http://zenodo.org/record/4917932